2005
DOI: 10.1002/pola.20954
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, crystallization, and morphology of star‐shaped poly(ε‐caprolactone)

Abstract: Six-arm star-shaped poly(e-caprolactone) (sPCL) was successfully synthesized via the ring-opening polymerization of e-caprolactone with a commercial dipentaerythritol as the initiator and stannous octoate (SnOct 2 ) as the catalyst in bulk at 120 8C. The effects of the molar ratios of both the monomer to the initiator and the monomer to the catalyst on the molecular weight of the polymer were investigated in detail. The molecular weight of the polymer linearly increased with the molar ratio of the monomer to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 44 publications
3
54
0
Order By: Relevance
“…[13,14] Dong et al reported the synthesis of starshaped PCL and poly[(lactic acid)-alt-(glycolic acid)] having three, four and six arms using multifunctional initiators such as trimethylolpropane, pentaerythritol and dipentaerythritol, respectively. [15][16][17][18] As an extension, the synthesis and physical properties of linear PCL-b-PLLA diblock copolymer were further studied as follows. Jérôme et al investigated the sequential block copolymerization of CL and other lactones or lactides using aluminum alkoxide as an initiator.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Dong et al reported the synthesis of starshaped PCL and poly[(lactic acid)-alt-(glycolic acid)] having three, four and six arms using multifunctional initiators such as trimethylolpropane, pentaerythritol and dipentaerythritol, respectively. [15][16][17][18] As an extension, the synthesis and physical properties of linear PCL-b-PLLA diblock copolymer were further studied as follows. Jérôme et al investigated the sequential block copolymerization of CL and other lactones or lactides using aluminum alkoxide as an initiator.…”
Section: Introductionmentioning
confidence: 99%
“…Tam et al [30] considered the peak at 603 cm −1 as it corresponds to the lactide ring deformation. Degee et al [31] used the peak at 935 cm −1 that corresponds to COO ring breathing mode as the characteristic peak and the shared band at 1383 cm −1 corresponding to the CH 3 deformation mode [32] as reference for the calculation of the residual monomer. Braun et al [23] discussed the peak at 1383 cm −1 and showed that this peak was not isolated, but overlapped with the C-H bending vibration.…”
Section: Molecular Weight Determinationmentioning
confidence: 99%
“…similar results for slow polymerization at lower catalyst concentration have been reported in the literature. [32] Thermal properties of the PLA products were evaluated using differential scanning calorimetry (DsC) as shown in Figure 9. A summery for the transitions is listed in Table 3.…”
Section: Molecular Weight Determinationmentioning
confidence: 99%
“…Star-shaped polymers, because of their higher segment density within the distance of their radius of rotation compared to that of linear polymers under the same conditions, have gained much more attention in recent years [9][10][11][12][13][14]. The excluded volume effects are more pronounced in star-shaped polymers, causing them to have low melting points.…”
Section: Introductionmentioning
confidence: 99%